2023
DOI: 10.15252/embj.2022113280
|View full text |Cite
|
Sign up to set email alerts
|

Embryo‐uterine interaction coordinates mouse embryogenesis during implantation

Abstract: Embryo implantation into the uterus marks a key transition in mammalian development. In mice, implantation is mediated by the trophoblast and is accompanied by a morphological transition from the blastocyst to the egg cylinder. However, the roles of trophoblast-uterine interactions in embryo morphogenesis during implantation are poorly understood due to inaccessibility in utero and the remaining challenges to recapitulate it ex vivo from the blastocyst. Here, we engineer a uterus-like microenvironment to recap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…Several epithelial growth factors (EGFs) and Integrins have been reported as molecules required for implantation ( Fritz et al, 2014 ; Aplin and Ruane, 2017 ). While the heparin-binding EGF-like growth factor (HB-EGF) has been suggested as the earliest molecule that mediates communication between the embryo and LE at the attachment ( Das et al, 1994 ) and ItgB1 may play a role in the invasion of mTE into LE ( Wang et al, 2002 ; Bondarenko et al, 2023 ), we need to examine the exact timing of their expression and function for further study. And many questions remain unanswered, such as the molecular basis of the attachment, the molecular mechanisms underlying the exchange of information between the blastocyst and the LE, and why the IC specifically protrudes toward the AM side.…”
Section: Discussionmentioning
confidence: 99%
“…Several epithelial growth factors (EGFs) and Integrins have been reported as molecules required for implantation ( Fritz et al, 2014 ; Aplin and Ruane, 2017 ). While the heparin-binding EGF-like growth factor (HB-EGF) has been suggested as the earliest molecule that mediates communication between the embryo and LE at the attachment ( Das et al, 1994 ) and ItgB1 may play a role in the invasion of mTE into LE ( Wang et al, 2002 ; Bondarenko et al, 2023 ), we need to examine the exact timing of their expression and function for further study. And many questions remain unanswered, such as the molecular basis of the attachment, the molecular mechanisms underlying the exchange of information between the blastocyst and the LE, and why the IC specifically protrudes toward the AM side.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, various research groups have invested in developing 3D platforms that would mimic the uterine environment. Recently published studies suggest promising outcomes in these 3D platforms ( Gu et al, 2022 ; Ichikawa et al, 2022 ; Bondarenko et al, 2023 ). In one study, it was demonstrated that 11% of retrieved mouse preimplantation embryos developed up to early organogenesis when cultured in a 3D platform ( Gu et al, 2022 ).…”
Section: Optimizing Culture Conditions For Extended Embryo Culture Us...mentioning
confidence: 99%
“…In vitro , confinement of cultured human embryonic stem cells to micro-patterned adhesive regions was sufficient to drive a self-organized pattern of cell differentiation into the 3 germ layers that arise during gastrulation [27]. More recently, in vitro culturing of mouse embryos using cavities of varying widths, has shown that both the geometry and the stiffness of the confining environment are important in driving and supporting fundamental processes such as axis polarization and cell lineage differentiation [28].…”
Section: Introductionmentioning
confidence: 99%